TRAINING FOR THE FUTURE TEACHER WITH THE HELP OF NEW PEDAGOGICAL TECHNOLOGIES (Pedagogy of Higher and Secondary Education, 2004)
The article deals with some problems concerning future teachers' professional training by means of new pedagogical technologies.